“Dragon, kung fu and Jackie Chan…”: stereotypes about China held by Malaysian students - Nikitina, Larisa; Furuoka, Fumitaka (Estonian Academy of Sciences and Tartu University, 2013)
Abstract. This study explored stereotypes about China held by young Malaysians. It focused on the learners of the Mandarin language in a big public university. The study not only examined the content but also assessed the favourability and salience of the language learners’ stereotypes, which had not been done in the previous studies. The stereotypes about China provided by the participants were diverse; they referred to culture, politics,language, history, climate, landscape, economics, religion and the Chinese people. Overall, the stereotypes were favourable. Especially the stereotypes referring to Chinese traditional and popular culture and cultural symbols were among the most frequent and most salient images of China. An interesting finding was that transnational popular culture played an important role in the formation of the stereotypical images about China. The study concludes by highlighting some pedagogical implications based on these findings. Keywords: country stereotypes, salience index, university students, Mandarin language, China, Malaysia